Clinical pregnancy rate for frozen embryo transfer with HRT: a randomized controlled pilot study comparing 1 week versus 2 weeks of oestradiol priming - Annalisa Racca; Samuel Santos-Ribeiro; Panagiotis Drakopoulos; Joran De Coppel; Lisbet Van Landuyt; Herman Tournaye; Christophe Blockeel (BMC, 2023)
Abstract Research question Does a frozen-embryo transfer in an artificially-prepared endometrium (FET-HRT) cycle yield similar clinical pregnancy rate with 7 days of oestrogen priming compared to 14 days? Design This is a single-centre, randomized, controlled, open-label pilot study. All FET-HRT cycles were performed in a tertiary centre between October 2018 and January 2021. Overall, 160 patients were randomized, with a 1:1 allocation, into two groups of 80 patients each: group A (7 days of E2 prior to P4 supplementation) and group B (14 days of E2 prior to P4 supplementation). Both groups received single blastocyst stage embryos on the 6th day of vaginal P4 administration. The primary outcome was the feasibility of such strategy assessed as clinical pregnancy rate, secondary outcomes were biochemical pregnancy rate, miscarriage rate, live birth rate and serum hormone levels on the day of FET. Chemical pregnancy was assessed by an hCG blood test 12 days after FET and clinical pregnancy was confirmed by transvaginal ultrasound at 7 weeks. Results The analysis included 160 patients who were randomly assigned to either group A or group B on the seventh day of their FET-HRT cycle if the measured endometrial thickness was above 6.5 mm. Following screening failures and of drop-outs, 144 patients were finally included both in group A (75 patients) or group B (69 patients). Demographic characteristics for both groups were comparable. The biochemical pregnancy rate was 42.5% and 48.8% for group A and group B, respectively (p 0.526). Regarding the clinical pregnancy rate at 7 weeks, no statistical difference was observed (36.3% vs 46.3% for group A and group B, respectively, p = 0.261). The secondary outcomes of the study (biochemical pregnancy, miscarriage, and live birth rate) were comparable between the two groups for IIT analysis, as well as the P4 values on the day of FET. Conclusions In a frozen embryo transfer cycle, performed with artificial preparation of the endometrium, 7 versus 14 days of oestrogen priming are comparable, in terms of clinical pregnancy rate; the advantages of a seven-day protocol include the shorter time to pregnancy, reduced exposure to oestrogens, and more flexibility of scheduling and programming, and less probability to recruit a follicle and have a spontaneous LH surge. It is important to keep in mind that this study was designed as a pilot trial with a limited study population as such it was underpowered to determine the superiority of an intervention over another; larger-scale RCTs are warranted to confirm our preliminary results. Trial registration Clinical trial number: NCT03930706.